PEMBINAAN AKHLAK SANTRI DI PESANTREN: STRATEGI PENDIDIKAN KARAKTER BERBASIS NILAI ISLAM - Rasti Astuti Laisaan; Muhammad Husni (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The moral development of students in Islamic boarding schools (pesantren) is an essential aspect of Islamic education, especially amidst the challenges of moral degradation, digital disruption, and social changes that influence the value systems of the younger generation. As Islamic educational institutions based on values ​​and traditions, pesantren play a strategic role in shaping the character of students based on Islamic values ​​while also being adaptive to current developments. This article aims to examine the conceptual model of moral development of students in Islamic boarding schools and the strategy of character education based on Islamic values ​​that are relevant to the contemporary context. This research uses a qualitative-descriptive approach through literature study (library research). Data were obtained from reputable journal articles, classic and contemporary books, and Islamic education policy documents. The results of the study indicate that the moral development of students in Islamic boarding schools is implemented through an integrative and holistic model, including role models (uswah ḥasanah), daily habits and discipline, spiritual strengthening through worship and etiquette, and support from the pesantren environment and culture as a hidden curriculum. The strategy of character education based on Islamic values ​​is strengthened through the synergistic integration of moral values ​​in formal, non-formal, and informal education. The conclusion of this article confirms that Islamic boarding schools (pesantren) possess structural and cultural advantages in sustainably fostering the moral character of their students. The Islamic boarding school moral development model contributes to the enrichment of Islamic character education theory and has the potential to serve as a conceptual reference for strengthening character education in a broader educational context.